Do donors value volunteer commitment in assessing nonprofit effectiveness? - Beck, Amanda W.; Garven, Sarah A.; Yetman, Michelle Higgins (Contemporary Accounting Research, 2025)
Abstract Evaluating organizational effectiveness is a significant challenge for nonprofit donors making donation allocation decisions. Donations may be misallocated if organizational effectiveness is inadequately assessed, and donors, who are often organizational outsiders, rely on nonprofit disclosures on IRS Form 990 to make such assessments. We examine whether donors value volunteer commitment, as measured by the number of volunteers that nonprofits disclose on Form 990, alongside financial and governance disclosures in assessing organizational effectiveness. Donors and volunteers prefer to make respective gifts of money and time to nonprofits that are effective in furthering their missions. Based on the premise that volunteers, as organizational insiders, are better positioned than donors to judge the impact of their contributions, we hypothesize that volunteer commitment provides value‐relevant information to donors for use in assessing imprecise effectiveness signals—namely, the program ratio and corporate governance disclosures. Consistent with this, we find that the value relevance of the program ratio and corporate governance disclosures to donors is increasing with the level of volunteer commitment. These results suggest that donors view volunteer commitment as a signal of effectiveness, useful in interpreting other signals of effectiveness. The evidence is more pronounced among nonprofits that report more credible volunteer disclosures, have a larger proportion of sophisticated donors, and are more complex. These findings have implications for regulators considering nonprofit disclosure policies, as well as nonprofit managers and directors engaging volunteers.